Philosophical analysis of models of engineering education in Russia; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Fadeeva V. N. Vera Nikolaevna (2016, 2016)
Title screen